2018
DOI: 10.1111/anae.14496
|View full text |Cite
|
Sign up to set email alerts
|

The association between attention deficit hyperactivity disorder and general anaesthesia ‐ a narrative review

Abstract: Summary Attention deficit hyperactivity disorder is a chronic neurodevelopmental disorder, manifesting primarily as attention deficit, hyperactivity and impulsive behaviour. General anaesthetics can be neurotoxic, affecting neuronal differentiation and synaptogenesis, which can lead to abnormalities of cognition, learning and behaviour. We hypothesise that exposure of the immature brain to general anaesthetics predisposes to the development of attention deficit hyperactivity disorder. In this review, we summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 60 publications
(100 reference statements)
0
22
0
Order By: Relevance
“…Anesthesia can induce neurotoxicity and neurocognitive impairments in young mice. 12 , 13 Previous data have shown that exposure to sevoflurane induces both learning deficits and abnormal social behaviors resembling autism spectrum disorders in neonatal mice. 14 , 15 Recent studies concluded that early exposure to anesthesia could have lasting effects on emotional and social development, and rodent behavioral models were an excellent instrument to investigate long-term socio-emotional general anesthesia-caused disorders in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia can induce neurotoxicity and neurocognitive impairments in young mice. 12 , 13 Previous data have shown that exposure to sevoflurane induces both learning deficits and abnormal social behaviors resembling autism spectrum disorders in neonatal mice. 14 , 15 Recent studies concluded that early exposure to anesthesia could have lasting effects on emotional and social development, and rodent behavioral models were an excellent instrument to investigate long-term socio-emotional general anesthesia-caused disorders in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ADHD show remarkable variation in complicating factors and neuropsychological weaknesses 5 . Previous studies suggested that the impaired development of dopaminergic neurons is related to ADHD development 6 . In addition to disorders in neurotransmitter system, other studies indicated that ADHD is caused by abnormal structural and functional synapses in mPFC 6,7 , which is responsible for behavioral inhibition and executive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the impaired development of dopaminergic neurons is related to ADHD development 6 . In addition to disorders in neurotransmitter system, other studies indicated that ADHD is caused by abnormal structural and functional synapses in mPFC 6,7 , which is responsible for behavioral inhibition and executive functions. Recently, clinical studies reported that repeated exposures to inhalational anesthetics in children is associated with the development of ADHD 6,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol abuse, anxious/depressed basal mood, low educational level and genetic susceptibility are identi ed as the risk factors for cognitive dysfunction [4,5]. Accumulating evidence revealed that anesthesia may provoke persistent abnormalities of neuronal circuits by affecting neuronal differentiation and synaptogenesis, and pharmacotoxic effects exacerbated the impairment of cognitive domains [6,7]. Sevo urane, as an inhaled volatile anesthetic agent, is widely used in pediatric practice [8].…”
Section: Introductionmentioning
confidence: 99%